Primary ciliary dyskinesia - Plavec Goran; Tomić Ilija; Škaro-Milić Anđelija B.; Radojčić Branko; Aćimović Slobodan (Vojnosanitetski Pregled)
In patients with chronic respiratory diseases that last since the early childhood, primary ciliary dyskinesia (PCD) needs to be considered. Four patients reviewed in this paper were with typical disease history and clinical picture, as well as clear ciliary axonema damage. Complete examination was performed in all the patients, including bronchoscopy with bronchography, and the examination of the biopsy samples of respiratory airways’ mucous membrane, obtained by transmission electron microscope (TEM). In two of the patients spermatozoa were also examined by TEM. Large anatomic deffects of airways were found in all the patients, but pulmonary function was normal (except in one case), representing one of PCD’s significant characteristics. First two cases fulfilled the criteria for Kartagener’s syndrome, which was initially sufficient for the diagnosis of PCD.